THE TRANSLATION PROCESS OF THE DIABETES SELF-MANAGEMENT QUESTIONNAIRE (DSMQ) INSTRUMENTS IN INDONESIAN - Fitri Andi Sabil; Liza Fauzia; Eva Arna Abrar; Nurul Reski Anisa (Universitas Karya Husada Semarang, 2024)
Measurement of patient capabilities in carrying out self-care can use the Diabetes Self-Management Questionnaire (DSMQ) instrument which includes some of the most important aspects of self-management, namely glucose management, diet control, physical activity, and the use of health care, but now the instrument is not yet available in The Indonesian version, so the instrument needs to go through the translation and back-translation process to used in the Bahasa version. This type of research is a descriptive study with translation and back-translation methods. There are no differences in the meaning of the results of the Third Translation Expert, only shows a change in the structure of the synthesis sentence that refers to the default Bahasa orders. DSMQ instruments have been through the translation process with the back-translation method which produces a good translation. Therefore, for the follow-up of this study, researchers recommend conducting validity and reliability tests to determine the feasibility of the instruments